2014
DOI: 10.1530/joe-14-0222
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin induces ductal cell dedifferentiation and β-cell neogenesis after 90% pancreatectomy

Abstract: Induction of b-cell mass regeneration is a potentially curative treatment for diabetes. We have recently found that long-term gastrin treatment results in improved metabolic control and b-cell mass expansion in 95% pancreatectomised (Px) rats. In this study, we investigated the underlying mechanisms of gastrin-induced b-cell mass expansion after Px. After 90%-Px, rats were treated with gastrin (PxCG) or vehicle (PxCV), pancreatic remnants were harvested on days 1, 3, 5, 7, and 14 and used for gene expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…Several studies have reported that H. pylori seropositivity was associated with different hormones [2,[8][9][10], most of which were involved in glucose metabolism directly or indirectly [11][12][13][14][15][16][17]. To our knowledge, at least three hormones supported our results, including gastrin, leptin and ghrelin.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have reported that H. pylori seropositivity was associated with different hormones [2,[8][9][10], most of which were involved in glucose metabolism directly or indirectly [11][12][13][14][15][16][17]. To our knowledge, at least three hormones supported our results, including gastrin, leptin and ghrelin.…”
Section: Discussionsupporting
confidence: 85%
“…Because of potential implications of gastrin in β-cell mass regeneration in rodents [Suarez-Pinzon et al 2008;Suissa et al 2013], a recent study evaluated the role of gastrin in promoting β-cell neogenesis from ductal cells in 90% Px rats [Tellez and Montanya, 2014]. In the gastrin-treated mice, strong proliferation activity was Xu et al [2006] In vivo Treatment with exendin-4 facilitated β-cell neogenesis in pancreatic ducts Tokui et al [2006] In vivo Betacellulin promoted ductal differentiation towards insulin-expressing cells Inada et al [2008] In vivo β-cell mass replenishment occurred from ductal cells 2 weeks post PDL Bonner-Weir et al [2008] In vivo Partial pancreatic tissue regeneration occurred from ductal cells Xu et al [2008] In vivo Re-expression of NGN3 in ductal lining cells occurred 1 week after PDL Criscimanna et al [2011] In vivo Proliferative ducts expressed acinar and endocrine markers 3/4 weeks post-DT injection Wang et al [2012] In vivo Administration of gastrin and EGF increased β-cell neogenesis Pfeifer et al [2013] In vivo Requirement of EMT for duct-lining cells differentiation into endocrine cells In vivo Continuous activation of NGN3 + cells along the lining duct occurred after ARX inhibition Téllez et al [2014] In vivo Appearance of β-cell clusters from ductal epithelium occurred 3 days post 90% Px Lemaire et al [2015] In vivo Bicaudal C1 expressed in duct lining cells was essential for progenitor differentiation Yamaguchi et al [2015] In vivo Pancreatic ductal glands contained niches of progenitor cells Carpino et al [2015] In vivo Pancreatic ductal glands as container of niches for pancreatic precursors Napolitano et al [2015] In vivo Continuous activation of NGN3 + cells along the lining duct occurred after PAX4 overexpression El-Gohary et al [2016] In vivo Duct-to-β-cell conversion occurred after partial Px in mice overexpressing TGF-β receptor Zhang et al [2016] In vivo Conversion of SOX9 + cells into insulin-producing cells occurred after administration of gastrin and EGF Seaberg et al [2004] In vitro Progenitor colonies arose from islet and ducts cultured with EGF and FGF2 Rovira et al [2010] In vitro Centroacinar/terminal ductal cells with progenitor-like phenotype ARX, aristaless related homeobox; DT, diphtheria toxin; EGF, epidermal growth factor; EMT, epithelial-mesenchymal transition; PDL, pancreatic duct ligation; Px, pancreatectomy; TGF, transforming growth factor.…”
Section: In Vivo Studies On Pancreatic Progenitorsmentioning
confidence: 99%
“…Ninety percent Px was performed as described previously (50). Briefly, animals were anesthetized with 5% isoflurane (Forane; Abbott) and maintained anesthetized with an isoflurane (1.5%) air mixture.…”
Section: Pancreatectomy and Pancreatic Remnant Harvestingmentioning
confidence: 99%
“…Thus, duct cell mass was determined using the traditional point-counting method on keratin 20-labeled sections (Table 1) (50). A nomogram relating number of points counted to volume density and expected relative standard error in percentage of mean (Ͻ10%) was used to determine the number of intercepts needed for a representative sampling (32).…”
Section: Morphometrymentioning
confidence: 99%
See 1 more Smart Citation